Low-cobalt high-voltage ternary positive electrode material and preparation method and application thereof
By using a technology of co-doping of a variety of metal compounds and surface gradient coatings in the ternary positive electrode material of lithium-ion batteries, the insufficient structural stability and safety problems at high voltages are solved, and higher battery performance and safety are achieved.
Patent Information
- Application Number
- CN202411706505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing lithium-ion battery ternary cathode materials have insufficient structural stability and safety problems under high voltage conditions, making it difficult to take into account both battery life, energy density and safety.
A variety of metal compounds are used to co-dopize in a certain proportion to form a surface gradient coating layer, and a fast ion solid electrolyte coating layer is built to improve the structural stability and safety performance of the positive electrode material.
The discharge specific capacity, first-time efficiency, safety performance, cycle performance and power performance of low-cobalt ternary cathode materials under high voltage conditions has been significantly improved.
Smart Images

Figure CN119517962A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery positive electrode raw materials and lithium ion battery application technology, and in particular to a low-cobalt high-voltage ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] With the current rapid development of 3C digital, electric tools and new energy vehicles around the world, the demand for lithium-ion batteries continues to increase. However, the core factors that affect or restrict the development of ion batteries are resources such as nickel, cobalt and lithium, among which lithium resources have a crucial impact on the cost of batteries and vehicles. It is difficult to fully balance the endurance, energy density and safety issues, which have a significant impact on high-voltage positive electrode materials. Through the study of multiple types of metal compounds and process methods, its composite modification and process optimization can improve the performance of high-voltage ternary positive electrode materials.
[0003] The development trend of ternary positive electrode materials for new energy lithium batteries is high voltage, single crystal, and high nickel. The insufficient structural stability and safety issues brought about by high voltage are huge challenges currently faced. Multi-element composite doping modification is used to improve structural stability, while improving the oxidation resistance of the particle surface under high voltage and surface phase defects, constructing surface gradient coating, fast ion conductor or solid coating layer, which is beneficial to improving the safety performance, cycle performance, rate performance, gram-to-weight capacity and first efficiency of high-voltage positive electrode materials. Summary of the invention
[0004] One of the purposes of the present invention is to provide a low-cobalt high-voltage ternary positive electrode material, which is co-doped with multiple metal compounds in a certain proportion, and then surface-gradient coated with other metal compounds to form a surface fast ion solid electrolyte coating layer. The finished ternary positive electrode material has good physical and chemical properties and application properties. The low-cobalt ternary positive electrode material has significantly improved discharge specific capacity, initial efficiency, safety performance, cycle performance and power performance under high voltage conditions.
[0005] A second object of the present invention is to provide a method for preparing the above-mentioned low-cobalt high-voltage ternary positive electrode material.
[0006] The third object of the present invention is to provide an application of the above-mentioned low-cobalt high-voltage ternary positive electrode material in the preparation of a secondary battery positive electrode sheet or a secondary battery.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a low-cobalt high-voltage ternary positive electrode material, comprising a core, and a first coating layer and a second coating layer sequentially coated on the surface of the core;
[0009] The chemical formula of the low-cobalt high-voltage ternary cathode material is Li a (Nix Co y Mn 1-x-y )(M) b O 2 , where 0.5≤x<1.0, 0<y≤0.10, 0.96≤a<1.14, 0<b≤0.15;
[0010] The M is selected from one or more of Zr, Al, Ce, Sr, Mg, Ti, Si, La, Ba, Ta, W, Co, Nb, Cr, Mo, Re, Ru, Zn, Ca, Y, In, Sn, F, B, C, and P;
[0011] Preferably, M is selected from a combination of Sr, Zr, Al, Nb, Ti, W, B and Ta.
[0012] The core formula is Li a (Ni x Co y Mn 1-x-y )(Sr c Al d Zr e Ti f Nb g W h B j ) 2 ; Among them, 0<c≤0.008, 0<d≤0.008, 0<e≤0.008, 0<f≤0.0065, 0<g≤0.0065, 0<h≤0.004, 0<i≤0.008.
[0013] The first coating layer has the general formula W x1 B y1 Al z1 O c1 , where x1 = 0.5 ~ 2.0, y1 = 1.0 ~ 5.0, z1 = 1.0 ~ 2.0, c1 = 1.0 ~ 3.0;
[0014] The second coating layer has the general formula of Li a1 Ta x2 O3, where a1=0.5~4, x2=1.0~3.0.
[0015] The low-cobalt high-voltage ternary positive electrode material is prepared by the following method: a ternary positive electrode material precursor is co-doped and modified by a compound dopant containing Sr / Zr / Al / Nb / Ti / W / B elements and sintered for the first time, and then crushed, screened and demagnetized to obtain a positive electrode material core Li a (Ni x Co y Mn 1-x-y )(Src Al d Zr e Ti f Nb g W h B j ) 2 ; Wherein, 0<c≤0.008, 0<d≤0.008, 0<e≤0.008, 0<f≤0.0065, 0<g≤0.0065, 0<h≤0.004, 0<i≤0.008;; Then the positive electrode material core is mixed with the first coating agent of the compound containing W / Al / B elements and sintered for the second time, and the positive electrode material after the first coating is obtained after crushing, screening and demagnetization; Finally, the positive electrode material after the first coating is mixed with the second coating agent of the compound containing Ta / Li elements and sintered for the third time, and the positive electrode material after the second coating is obtained after crushing, screening and demagnetization.
[0016] It also has stable layered structure characteristics and excellent overall battery performance at ≥4.40V.
[0017] Specifically, the present invention provides a method for preparing the above-mentioned low-cobalt high-voltage ternary positive electrode material, comprising the following steps:
[0018] (1) Ni x Co y Mn 1-x-y (OH) 2 (0.5≤x<1.0, 0<y≤0.10), lithium source, and compound dopant containing Sr / Zr / Al / Nb / Ti / W / B elements are mixed and sintered for the first time, and then crushed, sieved, and demagnetized to obtain the positive electrode material core Li a (Ni x Co y Mn 1-x-y )(Sr c Al d Zr e Ti f Nb g W h B j ) 2 ;
[0019] (2) mixing the positive electrode material core with a first coating agent of a compound containing W / Al / B elements, and then sintering for a second time, and then crushing, screening, and demagnetizing to obtain a positive electrode material after the first coating;
[0020] (3) The positive electrode material after the first coating is mixed with the second coating agent containing Ta / Li compound and then sintered for the third time, and then crushed, screened, demagnetized, and batch mixed to obtain the finished positive electrode material after the second coating.
[0021] Among them, the substances containing Zr, Al, Ce, Sr, Mg, Ti, Si, La, Ba, Ta, W, Co, Nb, Cr, Mo, Re, Ru, Zn, Ca, Y, In, Sn, F, B, C, and P in the raw materials are one or more of metal oxides, hydroxides, or halides.
[0022] The following is a detailed description:
[0023] Step (1):
[0024] Selection of ternary cathode material precursor, the particle size D 50 It can be 1.5-6.4 μm, preferably 1.8-5.2 μm.
[0025] The lithium source is selected from LiOH, LiOH·H 2 O. Li 2 CO 3 、LiNO 3 or C 2 H 3 O 2 One or more of Li, preferably LiOH or Li 2 CO 3 When used, the coarse lithium source particles can be mechanically ground to 2-10 μm or a lithium source of this specification on the market can be selected, preferably 3-5 μm.
[0026] In some embodiments, the ternary cathode material precursor Ni x Co y Mn 1-x-y (OH) 2 The ratio of the total molar amount of Ni, Co, and Mn in the lithium source, the molar amount of Li in the lithium source, and the total molar amount of Sr, Nb, Al, Zr, Ti, W, and B in the dopant is 1: (0.96~1.14): (0.0004-0.026), preferably 1: (0.98~1.10): (0.0008-~0.024), and more preferably 1: (0.99~1.08): (0.001~0.022).
[0027] In some embodiments, the dopant containing Sr / Nb / Al / Zr / Ti / W / B is a dopant containing γ-Al. 2 O 3 、SrZrO 3 、TiNb 2 O 7 and W.B. 4 mixture of
[0028] Preferably, the ternary cathode material precursor Ni xCo y Mn 1-x-y (OH) 2 With γ-Al 2 O 3 The mass ratio is 100:(0.02~-0.80), preferably 100:(0.06~0.70), more preferably 100:(0.08~0.60);
[0029] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y (OH) 2 With SrZrO 3 The mass ratio is 100: (0.03-0.90), preferably 100: (0.06-0.78), more preferably 100: (0.08-0.64);
[0030] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y (OH) 2 With TiNb 2 O 7 The mass ratio is 100:(0.015~-0.82), preferably 100:(0.04~0.66), more preferably 100:(0.06~0.58);
[0031] Preferably, the ternary cathode material precursor Ni x Co y Mn 1-x-y (OH) 2 With WB 4 The mass ratio is 100: (0.01-0.70), preferably 100: (0.04-0.60), more preferably 100: (0.06-0.50);
[0032] Preferably, γ-Al 2 O 3 Purity ≥ 99.9%, its D 50 Particle size 0.04 μm to 6 μm, preferably 0.1 μm to 5 μm, more preferably 0.4 μm to 3 μm;
[0033] Preferably, SrZrO 3 Purity ≥ 99.5%, its D 50 Particle size 0.05 μm to 5.0 μm, preferably 0.1 μm to 4.0 μm, more preferably 0.2 μm to 3.5 μm;
[0034] Preferably, TiNb 2 O 7 Purity ≥ 99.0%, its D50 Particle size 0.04 μm to 6.0 μm, preferably 0.06 μm to 5.0 μm, more preferably 0.3 μm to 3 μm;
[0035] Preferably, WB 4 Purity ≥ 99.5%, its D 50 The particle size is 0.2 μm to 5 μm, preferably 0.4 μm to 4 μm, and more preferably 0.5 μm to 2.5 μm.
[0036] In some embodiments, the mixing step uses a ball mill or a jar mill, a plowshare mixer or a high-speed mixer to mix the materials evenly, and then put them into a small dry pot or a sagger, shake them evenly and cut them into pieces before the first sintering.
[0037] In some embodiments, the first sintering step includes: heating to 700-1100° C. (preferably 720-1050° C., more preferably 740-980° C.) and keeping warm for 8-24 h (preferably 8-20 h, more preferably 9-18 h) in an oxygen-containing atmosphere (preferably the atmosphere is oxygen with a concentration of ≥95%);
[0038] Preferably, when the first sintering step is carried out in a muffle furnace or a tube furnace mode, the heating rate is controlled to be 1-5°C / min, preferably 2-4°C / min, and more preferably 3°C / min;
[0039] Preferably, when the first sintering step is carried out in an atmosphere roller kiln or a rotary kiln mode, the heating rate is controlled to be 1 to 30°C / h, preferably 5 to 20°C / h, and more preferably 10°C / h.
[0040] After the first sintering, the ternary positive electrode material-doped matrix (core) is obtained through coarse crushing, fine crushing, screening and demagnetization for subsequent coating.
[0041] Preferably, the particle size D50 of the ternary positive electrode material after crushing and sieving is 2 to 6 μm, preferably 2.2 to 4.6 μm.
[0042] Step (2):
[0043] In some embodiments, the ratio of the total molar amount of Ni, Co, and Mn in the core of the positive electrode material to the total molar amount of W, Al, and B in the first coating agent is 1:(0.0004-0.0120), preferably 1:(0.0006-0.011), and more preferably 1:(0.0008-0.009).
[0044] In some embodiments, the first coating agent containing W / Al / B elements is WB 4 、α-Al 2 O 3 and H3 BO 3 mixture of
[0045] Preferably, the positive electrode material core and WB 4 The mass ratio is 100: (0.02-0.80), preferably 100: (0.05-0.70), more preferably 100: (0.08-0.58);
[0046] Preferably, the positive electrode material core and α-Al 2 O 3 The mass ratio is 100:(0.01-0.60), preferably 100:(0.04-0.50), more preferably 100:(0.06-0.42);
[0047] Preferably, the positive electrode material core and H 3 BO 3 The mass ratio is 100:(0.02-0.90), preferably 100:(0.04-0.80), and more preferably 100:(0.06-0.70).
[0048] Preferably, WB 4 Purity ≥ 99.5%, its D 50 Particle size 100nm~200nm;
[0049] Preferably, α-Al 2 O 3 Purity ≥ 99.9%, its D 50 Particle size 80nm~160nm;
[0050] Preferably, H 3 BO 3 Purity ≥ 99.5%, its D 50 Particle size 1500~3000 mesh;
[0051] In some embodiments, the mixing step uses a ball mill or a jar mill, a plowshare mixer or a high-speed mixer to mix the materials evenly, and then put them into a small dry pot or a sagger, shake them evenly, cut them into pieces, and then sinter them for the second time.
[0052] In some embodiments, the second sintering step includes: heating to 380-740° C. (preferably 400-720° C., more preferably 420-700° C.) and keeping warm for 3-16 h (preferably 4-14 h, more preferably 5-12 h) in an oxygen-containing atmosphere (preferably the atmosphere is oxygen with a concentration of ≥95%);
[0053] Preferably, when the second sintering step is carried out in a muffle furnace or a tube furnace mode, the heating rate is controlled to be 1-3°C / min;
[0054] Preferably, when the second sintering step is carried out in an atmosphere roller kiln or a rotary kiln mode, the heating rate is controlled to be 1 to 20° C. / h.
[0055] Step (3):
[0056] In some embodiments, the ratio of the total molar amount of Ni, Co, and Mn in the positive electrode material after the first coating to the total molar amount of Ta and Li in the second coating agent is 1:(0.0001-0.0100), preferably 1:(0.0003-0.009), and more preferably 1:(0.0005-0.0080).
[0057] In some embodiments, the Ta / Li-containing second coating agent includes Ta 2 O 5 and anhydrous C 2 H 3 O 2 Li, or Ta(OH) 5 and anhydrous LiOH;
[0058] Preferably, the positive electrode material after the first coating is 2 O 5 The mass ratio is 100:(0.01-0.30), preferably 100:(0.03-0.24), more preferably 100:(0.05-0.20);
[0059] Preferably, the positive electrode material after the first coating is 2 H 3 O 2 The mass ratio of Li is 100:(0.04 to -1.50), preferably 100:(0.08 to 1.20), and more preferably 100:(0.1 to 0.96);
[0060] Preferably, Ta 2 O 5 Purity ≥ 99.9%, its D 50 Particle size 100nm~400nm;
[0061] Preferably, anhydrous C 2 H 3 O 2 Li purity ≥ 99.9%, its D 50 Particle size 60nm~150nm;
[0062] or,
[0063] Preferably, the positive electrode material after the first coating is Ta(OH) 5 The mass ratio is 100:(0.02-0.50), preferably 100:(0.07-0.42), more preferably 100:(0.1-0.38);
[0064] Preferably, the mass ratio of the positive electrode material after the first coating to the anhydrous LiOH is 100:(0.02-0.70), preferably 100:(0.04-0.56), and more preferably 100:(0.08-0.42);
[0065] Preferably, Ta(OH) 5 Purity ≥ 99.0%, its D 50 Particle size 100nm-400nm.
[0066] Preferably, the purity of anhydrous LiOH is ≥99.5%, and its D 50 Particle size 600nm~150nm;
[0067] In some embodiments, the mixing step uses a ball mill or a jar mill, a plowshare mixer or a high-speed mixer to mix the materials evenly, and then put them into a small dry pot or a sagger, shake them evenly, cut them into pieces, and then sinter them for the third time.
[0068] In some embodiments, the third sintering step includes: heating to 220-480° C. (preferably 240-470° C., more preferably 260-460° C.) and keeping warm for 2-12 h (preferably 3-11 h, more preferably 4-10 h) in an atmosphere containing dry air or oxygen-air combination (preferably the atmosphere is oxygen, with a concentration of ≥95%);
[0069] Preferably, when the third sintering step is carried out in a muffle furnace or a tube furnace mode, the heating rate of the step is controlled to be 1 to 5°C / min, preferably 2 to 4°C / min, and more preferably 3°C / min;
[0070] Preferably, when the third sintering step is carried out in an atmosphere roller kiln or rotary kiln mode, the heating rate of the step is controlled to be 1-20°C / h, preferably 5-15°C / h, and more preferably 10°C / h.
[0071] The positive electrode material after the second coating is crushed, screened, demagnetized, and can be mixed evenly in a batch mixing tank, and dry gas (dehydration and carbon dioxide removal) or inert gas is introduced for protection; the batch mixing equipment can be a ribbon batch mixer or a high-speed mixer.
[0072] Preferably, the particle size D of the finished positive electrode material after the second coating is 50 2.2~4.6μm.
[0073] In a third aspect, the present invention provides an application of the above-mentioned low-cobalt high-voltage ternary positive electrode material in the preparation of a secondary battery positive electrode sheet or a secondary battery.
[0074] Preferably, the secondary battery comprises a lithium-ion battery.
[0075] The present invention also discloses a secondary battery positive electrode sheet or a secondary battery prepared from the low-cobalt high-voltage ternary positive electrode material or the low-cobalt high-voltage ternary positive electrode material prepared by the method.
[0076] Technical effects:
[0077] The low-cobalt high-voltage ternary positive electrode material of the present invention is based on the traditional nickel-cobalt-manganese material with γ-Al 2 O 3 、SrZrO 3 、TiNb 2 O 7 and W.B. 4 Co-doping modification; jointly inhibiting cation mixing, increasing structural stability and mechanical strength under high voltage, improving the conductivity of the structural level, effectively promoting particle growth, and widening the interlayer spacing, improving its charge and discharge ion migration ability under high voltage and high rate; using γ-Al 2 O 3 It has a certain structural stability when treated at low temperature. Its catalytic reaction characteristics and the structural evolution characteristics of transforming to the stable α phase at high temperature can further improve the structure and thermal stability of the nickel-cobalt-manganese ternary material.
[0078] The low-cobalt high-voltage ternary positive electrode material of the present invention is γ-Al 2 O 3 、SrZrO 3 、TiNb 2 O 7 and W.B. 4 Co-doping modification is carried out, and Sr / Zr / Al / Nb / Ti / B / W is formed into cation co-doping through high-temperature sintering solid-phase reaction, which effectively increases the particle strength and improves the reversible capacity, reduces the side reactions at the interface between the active material and the electrolyte, reduces the solubility of manganese in the organic electrolyte, and effectively improves the material cycle performance under high voltage; it can also widen the ion channel and the interlayer distance, improve the material discharge efficiency and rate capability; improve the high-temperature electrochemical properties of the material, reduce the degree of Li / Ni mixing, and ensure the application performance of the battery product.
[0079] The low-cobalt high-voltage ternary positive electrode material of the present invention further adopts WB 4 , a-Al 2 O 3 and H 3 BO 3 The coating agent is modified by coating once; wherein, by using a-Al 2 O 3 、WB 4The coating improves the surface corrosion resistance of the ternary cathode material and the surface oxidation characteristics under high voltage. 3 BO 3 The low melting point characteristic promotes the diffusion and reaction of additives on the surface, and can effectively repair the surface particle morphology, improve surface conductivity, and reduce the impedance of the battery cell; at the same time, WB 4 , a-Al 2 O 3 and H 3 BO 3 After surface coating, it can react with residual lithium on the surface under high temperature solid phase synthesis conditions to generate Li-like 3 AB 2 O 6 , Li 2 WO 4 Fast ion conductors can effectively improve the surface conductivity and ion migration ability of materials; fast ion conductors and compounds containing W, B, and Al can improve the corrosion resistance of the particle surface against hydrofluoric acid, inhibit the generation and occurrence of microcracks, improve high-temperature oxidation resistance, reduce surface impedance, increase surface electronic conductivity, improve first discharge efficiency and cycle performance, and ensure the application performance of high-voltage battery products.
[0080] The low-cobalt high-voltage ternary positive electrode material of the present invention further adopts Ta 2 O 5 and anhydrous C 2 H 3 O 2 Li or Ta(OH) 5 and anhydrous LiOH as coating agents for secondary coating modification; among them, by using C 2 H 3 O 2 The low melting point characteristics of Li and LiOH can repair the surface particle morphology and improve SEM under appropriate conditions; at the same time, it can improve Ta 2 O 5 or Ta(OH) 5 The surface reaction and diffusion effects promote the formation of lithium tantalate-like fast ion solid electrolyte conductors on the surface, which can effectively improve the surface conductivity and ion migration ability of the material, further effectively inhibit the surface oxygen defect phase and the corrosion resistance of the particle surface, further improve the high-temperature oxidation resistance, reduce the surface impedance, increase the surface electronic conductivity, improve the first discharge efficiency and cycle performance, and ensure the application performance of high-voltage battery products.
[0081] The low-cobalt high-voltage ternary positive electrode material of the present invention adopts a composite modification method of multi-element co-doping and coating, and through the synergistic effect of composite synergistic doping containing Sr / Zr / Al / Nb / Ti / B / W compounds, primary coating containing W / B / Al compounds, and secondary coating containing Li / Ta compounds, the Li / Ni mixed arrangement and particle surface energy band effect in the positive electrode material are effectively improved, and the structural stability and thermal stability, rate / cycle / storage performance of the low-cobalt high-voltage single crystal ternary positive electrode material are improved, and the gram-specific capacity and first efficiency are improved, and the layered structure is more stable, the electronic conductivity is higher, the rate is more, the long cycle performance storage, and the low cost and high specific capacity are advantages. The lithium-ion battery prepared by the ternary positive electrode material provided by the present invention has a higher gram-specific capacity, rate, safety and cycle performance.
[0082] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 It is a schematic diagram of the structure of the ternary positive electrode material of the present invention;
[0084] Figure 2 The following is a flow chart of the preparation process of the ternary positive electrode material of the present invention;
[0085] Figure 3 The SEM morphology characteristics of the ternary cathode material prepared in Example 1-2;
[0086] Figure 4 This is the XRD characterization diagram of the ternary positive electrode material prepared in Example 1;
[0087] Figure 5 The charge and discharge curve diagram of the ternary positive electrode material prepared in Example 1-2;
[0088] Figure 6 The rate discharge curve of the ternary cathode material prepared in Example 1-2;
[0089] Figure 7 This is the cycle curve of the ternary positive electrode full battery prepared in Example 1. DETAILED DESCRIPTION
[0090] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0091] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0092] Example 1
[0093] A method for preparing a low-cobalt high-voltage ternary positive electrode material comprises the following steps:
[0094] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant SrZrO 3 (D 50 2.0±1.0μm), TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm), WB 4 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), SrZrO 3 (7.87g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3 (7.18g), WB 4 (4.02g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0095] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent WB 4 (D 50 140.0±20.0nm)(4.81g), H 3 BO 3 (D 502500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0096] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0097] Example 2
[0098] A method for preparing a low-cobalt high-voltage ternary positive electrode material comprises the following steps:
[0099] (1) Prepare the precursor Ni according to the conventional method 0.72 Co 0.05 Mn 0.23 (OH) 2 (D 50 3.0±0.5μm), LiOH·H 2 O(D 50 3.0±1μm) with dopant SrZrO 3 (D 50 2.0±1.0μm), TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm), WB 4 (D 501.5±0.5μm) raw materials, weigh Ni 0.72 Co 0.05 Mn 0.23 (OH) 2 (2000g), LiOH·H 2 O (870.0 g), SrZrO 3 (8.13g), TiNb 2 O 7 (8.60g), γ-Al 2 O 3 (7.94g), WB 4 (4.41g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 894°C for sintering for 11.0h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0100] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent WB 4 (D 50 140.0±20.0nm)(4.97g), H 3 BO 3 (D 50 2500 mesh) (5.97 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.78g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 670°C in an oxygen atmosphere, sintered for 8.4h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0101] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 5080.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0102] Comparative Example 1
[0103] The difference from Example 1 is that WB is not used. 4 Doping and synergistic coating, a method for preparing a positive electrode material, comprises the following steps:
[0104] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant SrZrO 3 (D 50 2.0±1.0μm), TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm), raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), SrZrO 3 (7.87g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3(7.18g); the material was transferred into a high-speed mixer, and the three powders were mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix was obtained;
[0105] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the three powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere and sintered for 8.6h. After cooling, it was crushed and sieved to remove magnetism to obtain a positive electrode material coated matrix;
[0106] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0107] Comparative Example 2
[0108] The difference from Example 1 is that WB is not used. 4 The method for preparing the positive electrode material by doping and synergistic coating without secondary coating modification comprises the following steps:
[0109] (1) Prepare the precursor Ni according to the conventional method 0.65 Co0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant SrZrO 3 (D 50 2.0±1.0μm), TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm), raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), SrZrO 3 (7.87g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. Under an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix was obtained;
[0110] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the three powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere and sintered for 8.6h. After cooling, it was crushed and sieved to remove magnetism to obtain a finished product coated with a positive electrode material;
[0111] (3) The obtained ternary positive electrode material is put into a VC mixing tank and mixed for 2 hours. The material is sieved and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis are performed.
[0112] Comparative Example 3
[0113] The difference from Example 1 is that SrZrO 3 and W.B. 4 Doping, a method for preparing a positive electrode material thereof, comprises the following steps:
[0114] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) and TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm), raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), SrZrO 3 (7.87g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. Under an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a ternary positive electrode material doped matrix was obtained;
[0115] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent WB 4 (D 50 140.0±20.0nm)(4.81g), H 3 BO 3 (D50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0116] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0117] Comparative Example 4
[0118] The difference from Example 1 is that SrZrO 3 Doping, WB 4 Coating, the preparation method of the positive electrode material comprises the following steps:
[0119] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm), WB4 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3 (7.18g), WB 4 (4.02g); the material was transferred into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. The powder was loaded into a crucible and then transferred into an atmosphere muffle furnace. The temperature was raised to 320°C at a rate of 2°C / min in an oxygen atmosphere for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0120] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the three powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere and sintered for 8.6h. After cooling, it was crushed and sieved to remove magnetism to obtain a positive electrode material coated matrix;
[0121] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 5080.0±10.0nm)(7.64g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0122] Comparative Example 5
[0123] The difference from Example 1 is that SrZrO 3 Doping, WB 4 Doping / coating, a method for preparing a positive electrode material thereof, comprises the following steps:
[0124] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant TiNb 2 O 7 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0125] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0126] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0127] Comparative Example 6
[0128] The difference from Example 1 is that SrZrO 3 Doping, WB 4 The method for preparing the positive electrode material of the doped / coated material without secondary coating comprises the following steps:
[0129] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant TiNb 2 O 7 (D 502.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), TiNb 2 O 7 (8.30 g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0130] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0131] (3) 1500 g of the obtained coated matrix sample was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100 rpm / 2 min, 1000 rpm / 30 min, and 200 rpm / 3 min. After being loaded into a crucible, it was transferred to an atmosphere muffle furnace and sintered at 340 ° C for 6.4 h in a dry air atmosphere. After cooling, it was crushed and sieved to remove magnetism; the obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2 h. The material was sieved, demagnetized, and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0132] Comparative Example 7
[0133] The difference from Example 1 is that TiNb 2 O7 and W.B. 4 Doping, a method for preparing a positive electrode material thereof, comprises the following steps:
[0134] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant SrZrO 3 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), SrZrO 3 (7.87g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0135] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent WB 4 (D 50 140.0±20.0nm)(4.81g), H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0136] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0137] Comparative Example 8
[0138] The difference from Example 1 is that TiNb 2 O 7 Doping and WB 4 Doping / coating, a method for preparing a positive electrode material thereof, comprises the following steps:
[0139] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant SrZrO 3 (D 50 2.0±1.0μm), γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li2 CO 3 (764.10g), SrZrO 3 (7.87g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0140] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0141] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0142] Comparative Example 9
[0143] The difference from Example 1 is that SrZrO 3 / TiNb2 O 7 / WB 4 Doping, a method for preparing a positive electrode material thereof, comprises the following steps:
[0144] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0145] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent WB 4 (D 50 140.0±20.0nm)(4.81g), H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0146] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0147] Comparative Example 10
[0148] The difference from Example 1 is that SrZrO 3 / TiNb 2 O 7 / WB 4 Doping and WB 4 Coating, the preparation method of the positive electrode material comprises the following steps:
[0149] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), γ-Al 2 O 3(7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0150] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0151] (3) Sample 1500 g of the obtained coated substrate and mix it with the coating agent Ta 2 O 5 (D 50 200.0±20.0nm)(2.15g), C 2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and the powders were mixed evenly in a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, it was crushed and sieved for demagnetization. The obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2h. The discharged material was sieved for demagnetization and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0152] Comparative Example 11
[0153] The difference from Example 1 is that only γ-Al 2 O 3 Doping and α-Al 2 O 3 Coating, the preparation method of the positive electrode material comprises the following steps:
[0154] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) with dopant γ-Al 2 O 3 (D 50 1.5±0.5μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g), γ-Al 2 O 3 (7.18g); the material was transferred into a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred into an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material doped matrix was obtained;
[0155] (2) 1600 g of the obtained doped matrix was sampled and mixed with the coating agent α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min. After being put into a crucible, it was transferred into an atmosphere muffle furnace, heated to 680℃ in an oxygen atmosphere, sintered for 8.6h, cooled, crushed, and sieved to remove magnetism, to obtain a positive electrode material coated matrix;
[0156] (3) 1500 g of the obtained coated matrix sample was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100 rpm / 2 min, 1000 rpm / 30 min, and 200 rpm / 3 min. After being loaded into a crucible, it was transferred to an atmosphere muffle furnace and sintered at 340 ° C for 6.4 h in a dry air atmosphere. After cooling, it was crushed and sieved to remove magnetism; the obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2 h. The material was sieved, demagnetized, and packaged to obtain the finished positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0157] Comparative Example 12
[0158] The difference from Example 1 is that only one coating modification is performed. The preparation method of the positive electrode material comprises the following steps:
[0159] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g); the material was transferred to a high-speed mixer, and the powder was mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred to an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material-sintered matrix was obtained;
[0160] (2) Take 1600 g of the obtained doped matrix and mix it with the coating agent WB 4 (D 50 140.0±20.0nm)(4.81g), H 3 BO 3 (D 50 2500 mesh) (5.54 g), α-Al 2 O 3 (D 50 120.0±20.0nm)(3.64g) was put into a high-speed mixer, and the three powders were mixed evenly at 100rmp / 2min, 1200rpm / 30min, and 200rmp / 3min in a three-stage mode, and then loaded into a crucible, heated to 680°C and sintered for 8.6h in an oxygen atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a positive electrode material coated matrix;
[0161] (3) 1500 g of the obtained coated matrix sample was put into a high-speed mixer, and the powder was mixed evenly in a three-stage mode of 100 rpm / 2 min, 1000 rpm / 30 min, and 200 rpm / 3 min. The powder was then loaded into a crucible and sintered at 340 ° C for 6.4 h in a dry air atmosphere. After cooling, it was crushed and sieved to remove magnetism; the obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2 h. The material was sieved, demagnetized, and packaged to obtain the finished ternary positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were performed.
[0162] Comparative Example 13
[0163] The difference from Example 1 is that only secondary coating modification is performed, and the preparation method of the positive electrode material comprises the following steps:
[0164] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g); the material was transferred to a high-speed mixer, and the three powders were mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred to an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material-sintered matrix was obtained;
[0165] (2) 1600 g of the obtained doped matrix sample was put into a high-speed mixer, and mixed evenly according to the three-stage mode of 100 rpm / 2 min, 1200 rpm / 30 min, and 200 rpm / 3 min. The mixture was put into a crucible, heated to 680° C. and sintered for 8.6 h in an oxygen atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a second sintered positive electrode material matrix;
[0166] (3) 1500 g of the obtained calcined matrix was sampled and coated with a coating agent Ta. 2 O 5 (D 50 200.0±20.0nm)(2.15g), C2 H 3 O 2 Li(D 50 80.0±10.0nm)(7.64g) was put into a high-speed mixer and mixed evenly at a three-stage mode of 100rmp / 2min, 1000rpm / 30min and 200rmp / 3min. The three powders were then put into a crucible and sintered at 340°C for 6.4h in a dry air atmosphere. After cooling, the powders were crushed and sieved for demagnetization. The obtained ternary cathode material was put into a VC mixing tank and mixed for 2h. The product was sieved, demagnetized and packaged to obtain the finished ternary cathode material. The relevant physical and chemical performance characterization tests and data analysis were carried out.
[0167] Comparative Example 14
[0168] The difference from Example 1 is that no doping and primary / secondary coating modification are performed. The preparation method of the positive electrode material comprises the following steps:
[0169] (1) Prepare the precursor Ni according to the conventional method 0.65 Co 0.07 Mn 028 (OH) 2 (D 50 3.4±0.5μm), Li 2 CO 3 (D 50 3.5±1μm) raw materials, weigh Ni 0.65 Co 0.07 Mn 028 (OH) 2 (2000g), Li 2 CO 3 (764.10g); the material was transferred to a high-speed mixer, and the three powders were mixed evenly using a three-stage mode of 200rmp / 2min, 800rpm / 20min, and 100rmp / 3min. After being loaded into a crucible, it was transferred to an atmosphere muffle furnace. In an oxygen atmosphere, the temperature was raised to 320°C at a rate of 2°C / min for sintering for 3.2h, then raised to 770°C for sintering for 3.6h, and then raised to 952°C for sintering for 12.4h; after cooling, crushing and sieving, a positive electrode material-sintered matrix was obtained;
[0170] (2) 1600 g of the obtained doped matrix sample was put into a high-speed mixer, and mixed evenly according to the three-stage mode of 100 rpm / 2 min, 1200 rpm / 30 min, and 200 rpm / 3 min. The mixture was put into a crucible, heated to 680° C. and sintered for 8.6 h in an oxygen atmosphere, and then crushed and sieved to remove magnetism after cooling to obtain a second sintered positive electrode material matrix;
[0171] (3) 1500 g of the obtained dialkyl matrix was sampled and put into a high-speed mixer according to the three-stage mode of 100 rpm / 2 min, 1000 rpm / 30 min, and 200 rpm / 3 min. After mixing evenly, it was loaded into a crucible and sintered at 340 ° C for 6.4 h in a dry air atmosphere. After cooling, it was crushed and sieved to remove magnetism; the obtained ternary positive electrode material was put into a VC mixing tank and mixed for 2 h. The material was sieved, demagnetized, and packaged to obtain the finished ternary positive electrode material, and relevant physical and chemical performance characterization tests and data analysis were carried out.
[0172] Experimental example
[0173] 1. Physical and chemical indicators
[0174] The positive electrode materials prepared in the above Examples 1-2 and Comparative Examples 1-14 were respectively tested for element and impurity content, and the physical and chemical indicators of the samples were analyzed using relevant equipment such as a scanning electron microscope, a laser particle size instrument, and a Swiss Metrohm automatic titration instrument familiar to technicians. The test results are shown in Table 1 below.
[0175] The SEM images of the ternary cathode materials prepared in Examples 1-2 are shown in Figure 3 The ternary cathode material prepared in Example 1 was further characterized by XRD, and the characterization results are shown in Figure 4 .
[0176] Table 1 Physical and chemical index results of ternary positive electrode materials of Examples 1-2 and Comparative Examples 1-14
[0177]
[0178] It can be seen that the basic physical and chemical index test data of Ni6507 and Ni7205 in Examples 1-2 and Comparative Examples 1-14 show that the performance indicators related to tap compaction, pH, and residual alkali are improved, the tap density is increased, the pH and residual alkali content are reduced, and the materials have better comprehensive performance advantages.
[0179] 2. Electrical performance and cycle performance test
[0180] The positive electrode materials prepared in Examples 1-2 and Comparative Examples 1-14 were prepared into lithium-ion batteries (active material: PVDF:CNT:SP=97.2:1.1:0.8:0.9, solid content 73.5%) using methods well known to those skilled in the art, and the obtained positive electrode materials were assembled into button batteries.
[0181] Using the blue electric test system, the first charge and discharge specific capacity (see Example 1-2) was measured in the voltage range of 3.0-4.60V at 25°C and 0.1C. Figure 4(a)-(b)) and 0.2C / 0.5C / 1.0C / 2.0C rate charge / discharge performance (see Example 1-2 Figure 6 The results are shown in Table 2 below.
[0182] Table 2 Rate discharge / cycle performance test results
[0183]
[0184] It can be seen that by comparing the buckle test data made of Ni6507 and Ni7205 in Examples 1-2 with the ternary positive electrode single crystal materials in Comparative Examples 1-14, it is reflected that the higher gram-to-gram capacity and rate discharge performance, the buckle cycle performance has obvious advantages; and under 1C charge and discharge conditions, Example 1 and Comparative Example 1 are prepared into PIE-116103322-61Ah soft-pack batteries (containing natural graphite for the negative electrode, 9+2+2 wet-process ceramic diaphragm, and HDGT electrolyte with its own formula) according to the battery cell manufacturing process for full battery production and cycle performance testing. Example 1 has a room temperature cycle of 2000 weeks ≥88%, a high temperature cycle of 1380 weeks ≥84%, and Comparative Example 1 has a room temperature cycle of 1300 weeks ≥80%, and a high temperature cycle of 650 weeks ≥82%; It can be seen that the cycle performance of the scheme described in the present invention is significantly improved year-on-year, and the test results are shown in Figure 7 shown.
[0185] It can be seen that the gram-to-gram capacity of the ternary positive electrode material prepared by the present invention has increased year-on-year, and the rate discharge performance and cycle performance have been improved, and it has excellent all-electric application performance.
[0186] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A low-cobalt high-voltage ternary cathode material, characterized in that: It comprises an inner core, and a first coating layer and a second coating layer sequentially coating the inner core surface outwardly; The chemical formula of the core, the first and the second coating layers of the low-cobalt high-voltage ternary positive electrode material is Li a (Ni x Co y Mn 1-x-y )(M) b O2, where 0.5≤x<1.0, 0<y≤0.10, 0.96≤a<1.14, 0<b≤0.15; The M is selected from one or more of Zr, Al, Ce, Sr, Mg, Ti, Si, La, Ba, Ta, W, Co, Nb, Cr, Mo, Re, Ru, Zn, Ca, Y, In, Sn, F, B, C, and P.
2. A low-cobalt, high-voltage ternary positive electrode material as claimed in claim 1, further characterized in that M is selected from the group consisting of Sr, Zr, Al, Nb, Ti, W, B and Ta.
3. A low-cobalt high-voltage ternary cathode material as claimed in claim 1, further characterized in that the core general formula is Li a (Ni x Co y Mn 1-x-y )(Sr c Al d Zr e Ti f Nb g W h B j )O2; where 0<c≤0.008,0<d≤0.008,0<e≤0.008,0<f≤0.0065,0<g≤0.0065,0<h≤0.004,0<j≤0.008; The first coating layer has the general formula W x1 B y1 Al z1 O c1 , where x1 = 0.5 ~ 2.0, y1 = 1.0 ~ 5.0, z1 = 1.0 ~ 2.0, c1 = 1.0 ~ 3.0; The second coating layer has the general formula of Li a1 Ta x2 O3, where a1=0.5~4, x2=1.0~3.
0.
4. A low-cobalt high-voltage ternary positive electrode material as claimed in claim 1, characterized in that: The preparation method is as follows: a ternary positive electrode material precursor is co-doped and modified with a compound dopant containing Sr / Zr / Al / Nb / Ti / W / B elements and subjected to the first sintering, and the positive electrode material core is obtained after crushing, screening and demagnetization; then the positive electrode material core is mixed with a first compound coating agent containing W / Al / B elements and subjected to the second sintering, and the positive electrode material after the first coating is obtained after crushing, screening and demagnetization; finally, the positive electrode material after the first coating is mixed with a second compound coating agent containing Ta / Li elements and subjected to the third sintering, and the positive electrode material after the second coating is obtained after crushing, screening and demagnetization.
5. A method for preparing the low-cobalt high-voltage ternary positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: (1) Ni x Co y Mn 1-x-y (OH)2 (0.5≤x<1.0, 0<y≤0.10), lithium source, and compound dopant containing Sr / Zr / Al / Nb / Ti / W / B elements are mixed and sintered for the first time, and then crushed, sieved, and demagnetized to obtain the positive electrode material core Li a (Ni x Co y Mn 1-x-y )(Sr c Al d Zr e Ti f Nb g W h B j )O2; (2) mixing the positive electrode material core with a first coating agent of a compound containing W / Al / B elements, and then sintering for a second time, and then crushing, screening, and demagnetizing to obtain a positive electrode material after the first coating; (3) The positive electrode material after the first coating is mixed with the second coating agent of the compound containing Ta / Li elements and then sintered for the third time, and then crushed, screened, demagnetized, and batch mixed to obtain the finished positive electrode material after the second coating.
6. The method for preparing a low-cobalt high-voltage ternary cathode material according to claim 5, further characterized in that, in step (1), The lithium source is one or more selected from LiOH, LiOH·H2O, Li2CO3, LiNO3 or C2H3O2Li; preferably LiOH or Li2CO3; The doping element compound containing Sr / Zr / Al / Nb / Ti / W / B is selected from SrCO3, SrTiO3, SrO, ZrO2, Zr 0.92 O2Y 0.08 、One or two or more of the oxides, hydroxides or halides of ZrB2, SrZrO3, TiNb2O7, NbO2, TiO2, WO3, WB, W2B, WB4, W2B5, H2WPO4, Al2O3, AlF3, Al(OH)3, AlCl3, AlBr3, LiAlH4, Al(BH4)3, AlB2, AlPO4, Al(H2PO4)3, B2O3, H3BO3, NaAlO2, NaAlCl4, Na3AlF6, LiOH, LiNbO3; The W / Al / B / Ta / Li coating element compound is one or two or more of the oxides, hydroxides or halides selected from Al2O3, AlB2, AlF3, Al(OH)3, WB, W2B, WB4, WO3, H2WPO4, Ta2O5, Ta(OH)5, TaF5, TaCl5, TaBr5, Tal5, B2O3, H3BO3, C2H3O2Li, Li3BO3, Li2WO4, LiAlO2, Li2TiO3, LiTaO3, and Li3PO4.
7. The method for preparing a low-cobalt high-voltage ternary positive electrode material according to claim 5 or 6, further characterized in that, in step (1), the ratio of the total molar amount of Ni, Co, and Mn in the ternary positive electrode material precursor, the molar amount of Li in the lithium source, and the total molar amount of Sr, Nb, Al, Zr, Ti, W, and B in the dopant is 1: (0.96-1.14): (0.0004-0.026), preferably 1: (0.98-1.10): (0.0008-0.024), and more preferably 1: (0.99-1.08): (0.001-0.022); in step (2) , the ratio of the total molar amount of Ni, Co, and Mn in the core of the positive electrode material to the total molar amount of W, Al, and B in the first coating agent is 1:(0.0004-0.012), preferably 1:(0.0006-0.011), and more preferably 1:(0.0008--0.009); in step (3), the ratio of the total molar amount of Ni, Co, and Mn in the positive electrode material after the first coating to the total molar amount of Ta and Li in the second coating agent is 1:(0.0001-0.0100), preferably 1:(0.0003-0.009), and more preferably 1:(0.0005-0.0080).
8. The method for preparing a low-cobalt, high-voltage ternary positive electrode material according to claim 5 or 6, further characterized in that the dopant containing Sr / Nb / Al / Zr / Ti / W / B elements is a mixture of γ-Al2O3, SrZrO3, TiNb2O7 and WB4; the first coating agent containing W / Al / B elements is a mixture of WB4, a-Al2O3 and H3BO3; the second coating agent containing Ta / Li includes a mixture of Ta2O5 and anhydrous C2H3O2Li, or a mixture of Ta(OH)5 and anhydrous LiOH.
9. The method for preparing a low-cobalt high-voltage ternary cathode material according to claim 8, further characterized in that: In step (1), Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to γ-Al2O3 is 100:(0.02-0.80), preferably 100:(0.06-0.70), more preferably 100:(0.08-0.60); Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to SrZrO3 is 100:(0.03-0.90), preferably 100:(0.06-0.78), more preferably 100:(0.08-0.64); Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to TiNb2O7 is 100:(0.015-~0.82), preferably 100:(0.04~0.66), more preferably 100:(0.06~0.58); Ternary cathode material precursor Ni x Co y Mn 1-x-y The mass ratio of (OH)2 to WB4 is 100:(0.01-0.70), preferably 100:(0.04-0.60), more preferably 100:(0.06-0.50); Preferably, in step (1), the first sintering comprises: heating to 700-1100° C. and keeping the temperature for 8-24 hours in an oxygen-containing atmosphere; In step (2), the mass ratio of the positive electrode material core to WB4 is 100:(0.02-0.80), preferably 100:(0.05-0.70), and more preferably 100:(0.08-0.58); The mass ratio of the positive electrode material core to α-Al2O3 is 100:(0.01-0.60), preferably 100:(0.04-0.50), and more preferably 100:(0.06-0.42); The mass ratio of the positive electrode material core to H3BO3 is 100:(0.02-0.90), preferably 100:(0.04--0.80), and more preferably 100:(0.06-0.70); Preferably, in step (2), the second sintering comprises: heating to 380-740° C. and maintaining the temperature for 3-16 hours in an oxygen-containing atmosphere; In step (3), preferably, the mass ratio of the positive electrode material after the first coating to Ta2O5 is 100:(0.01-0.30), preferably 100:(0.03-0.24), and more preferably 100:(0.05-0.20); The mass ratio of the positive electrode material after the first coating to the anhydrous C2H3O2Li is 100:(0.04-1.50), preferably 100:(0.08-1.20), and more preferably 100:(0.1-0.96); Or, preferably, the mass ratio of the positive electrode material after the first coating to Ta(OH)5 is 100:(0.02-0.50), preferably 100:(0.07-0.42), more preferably 100:(0.1-0.38); The mass ratio of the positive electrode material after the first coating to the anhydrous LiOH is 100:(0.02-0.70), preferably 100:(0.04-0.56), and more preferably 100:(0.08-0.42); Preferably, in step (3), the third sintering comprises: heating to 220-480° C. and maintaining the temperature for 2-12 hours in an atmosphere containing dry air or oxygen-air combination.
10. Use of the low-cobalt high-voltage ternary positive electrode material according to any one of claims 1 to 4 or the low-cobalt high-voltage ternary positive electrode material prepared by the preparation method according to any one of claims 5 to 9 in preparing a secondary battery positive electrode sheet or a secondary battery; preferably, the secondary battery is a lithium-ion battery.
Citation Information
Patent Citations
Nickel-rich positive electrode material with three-layer core-shell structure for power and preparation method of nickel-rich positive electrode material
CN114204003A
High-nickel ternary positive electrode material and preparation method thereof
CN116031389A
Positive electrode material, preparation method thereof and lithium ion battery
CN117613230A
Multi-element modified single-crystal positive electrode material, preparation method thereof, lithium ion battery and power utilization device
CN118943317A
Low-gas-production and long-cycle life single crystal ternary positive electrode material and preparation method therefor
WO2024067685A1
Cited By
High-nickel positive electrode material as well as preparation method and application thereof
CN121306991A